A Note on Certain Aspects of Irrigation in Ceylon - Planning Commission (Planning Commission Government of India, 1969)
The note on irrigation in Ceylon, authored by Shri Balwant Singh Nag in 1962, evaluates the state, challenges, and potential of irrigation programs in the country. The report highlights the critical role of irrigation in enhancing paddy production, food security, and economic stability, particularly given the projected rice imports under the Ten-Year Plan (1959–68). Ceylon possesses 3.25 million acres of gross land suitable for irrigation, with development potential of about 2 million acres, yet as of 1960, only 751,375 acres were irrigated, leaving the majority of paddy cultivation dependent on rainfall. Seasonal irrigation practices differ in impact: the Maha season provides minimal yield benefits, serving mostly as a safeguard against erratic rainfall, while irrigation during the Yala season is essential, especially in the Dry Zone. The report notes the high financial costs of major irrigation projects, delayed construction timelines, and insufficient water pricing, emphasizing the need for cost assessment and economic viability. Recommendations include synchronized construction schedules, efficient water use, and crop diversification to maximize returns on irrigation investments. The study concludes that optimizing water use, streamlining project execution, and integrating economic considerations are crucial to improving the effectiveness and productivity of Ceylon’s irrigation infrastructure.
Planning Commission Government of India April, 1962
Keywords: Ceylon; Irrigation; Paddy Production; Dry Zone; Wet Zone; Ten-Year Plan; Agricultural Yield; Water Management; Irrigation Projects; Economic Viability; Crop Diversification; Infrastructure Development